THE POSSIBILITIES OF USING FORESIGHT SESSIONS IN WORKING OUT “LIPETSK-2035” CITY DEVELOPMENT STRATEGY - Z. V. Korneva; I. S. Grab; T. YU. Ismailova; I. S. Rakitina (Управленческие науки, 2017)
Elaboration of the city development strategic planning tools for the long term period is currently rather an actual problem. This is due to several reasons, the most significant of which are the need of overcoming the dependence of the city on the city-forming enterprise activity and willingness to global changes associated with the advent of post-industrial integral civilization. The strategic plan of the city development for the period till 2035 should prepare the city socio-economic system for the inevitable changes due to what the decision was made to organize a series of the foresight sessions while the preparations for the developing a strategy. The experience has shown the feasibility of these methods in identifying the trends and technologies that provide the potential socio-economic system contour of the future.